"I need to skip a song because it sucks": Exploring mobile phone use while driving among young adults. (October 2018) - George, Amanda M.; Brown, Patricia M.; Scholz, Brett; Scott-Parker, Bridie; Rickwood, Debra
Highlights: Online survey revealed most common phone function for young adults while driving was music. Differences in phone functions while driving were identified by licence type. Focus group themes for phone use while driving were for entertainment, to connect and navigation. Targeted interventions should acknowledge the multiple phone functions used while driving. Abstract: Background: Mobile phone use while driving is a well-recognized area of concern. However, while texting/calling among young adult drivers has received much research attention, more research is needed regarding other phone functions used by young adults while driving. Study aim: To explore mobile phone functions used by young adult drivers while driving. Results: An online survey of 17–24 year old drivers ( N = 612; 428 females) and focus groups with drivers aged ( N = 18; 8 females) revealed that mobile phone use while driving was a very common behavior, with more full licence drivers compared with Learner/Provisional drivers using their phone to make/answer calls, send/read text messages and for internet browsing. This nature of mobile phone use while driving was varied, with phones commonly used for entertainment (e.g., to play music), to connect with others (via texting and/or voice calls) and for navigation. Concluding remarks: Young adults use a variety of functions on their phone while driving. It is important that young driver-targeted intervention efforts acknowledge that multiple functions of the mobile phone are used during the drive and it serves multiple purposes. Examining the inhibitors and facilitators of mobile phone use and its various functions while driving is needed, in addition to elucidating if the usage of particular mobile phone functions is similar across different driver cohorts.